Whispering gallery mode microlaser based on a single polymer fiber fabricated by electrospinning. (6th September 2019) - Chen, Xianxian; Xie, Kang; Hu, Taoping; Zhang, Xiaojuan; Yang, Yong; Ma, Jiajun; Zhang, Junxi; Cheng, Xusheng; Hu, Zhijia
Abstract: Electrospinning is a very simple method of preparing polymer solutions into high performance fibers. In this work, PM597-doped polymer fibers with different diameters have been fabricated by electrospinning technology. Whispering gallery mode (WGM) lasing emission was observed when a 532 nm pulse laser beam radially excited the single electrospun polymer fiber (EPF) created by this method. The distribution of WGMs is also quantitatively confirmed through theoretical calculation. Additionally, the number of WGM laser peaks decrease as the diameter of the EPF decreases. Single longitudinal mode laser emission can be obtained when the EPF diameter decreases to 8.8 µ m. It has also been found that the WGM laser from the single EPF has relatively low thresholds and good lifetime compared to droplet lasers or other fiber lasers. Moreover, EPF networks have unique research prospects in photonic devices, optical pump lasers and biosensing due to their very large surface to volume ratio.